Viability of an Integrated Farm as an Agritourism Site in Toboso, Negros Occidental inthe New Normal - Benignos, Kenneth T.; Estores, Kristin Iris G. (Technium Social Sciences Journal, 2022)
Agritourism is the perception of the two sustainable development goals, Goal No. 2 on Zero Hunger and Goal No. 8 on inclusive economic growth, leadingtoagriculture policy reform that encourages farm operation diversification through tourismtogenerate income. The integrated farm is very much related to agritourism. Its various existingagricultural enterprises will create different activities and attractions for visitors that areunique and different from other types of tourist attractions, a powerful tool for enhancingprofitability. So far, no agritourism study and program has been conducted nor implementedin Toboso, Negros Occidental. Hence, the study assessed the viability of the internal (management, technical, marketing, socioeconomic and environmental) and external (opportunities and challenges) factors of Salamanca Organics Integrated Farm(SOIF) asanagritourism site and to assess the financial performance as an agricultural productionfarm. The descriptive research design was utilized to determine the viability of Salamanca OrganicsIntegrated Farm (SOIF) as an agritourism site. The primary data was collected usingaresearcher-made questionnaire which was accomplished by 183 participants composedoftourists selected by random sampling and complete enumeration sample to obtain the dataofthe barangay council, tourism development experts, farm owners, and SOIFowners. Secondary data analysis on the farm’s financial performance was presented in financial ratios(profitability, liquidity, and solvency) from the audited financial statement. The overall findings revealed that all factors (internal factors: management, technical, environmental, marketing and socioeconomics and external factors: opportunities and challenges) wereveryhighly viable that imposed the viability of Salamanca Organics Integrated Farm(SOIF) asanagritourism site. However, the financial performance described by the financial ratios(profitability, solvency, and liquidity) of the farm revealed weak financial performanceasaproduction farm, implying that farm operation was financed by debts and resource translationto profit and wealth was struggling. The findings provide information and data tofarmowners and local government officials as a basis for an agritourism viability action plan.